1996
DOI: 10.1016/0735-1097(96)00233-1
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of spontaneous occurrence of sustained monomorphic ventricular tachycardia in right ventricular dysplasia

Abstract: Increased heart rate and shortening of the coupling intervals of the first cycles before the tachycardia are due to a change in the vagosympathetic balance with an increased sympathetic tone. This increase appears to be the main determinant of the ventricular tachycardia in this disease in contrast to the multifactorial origin of ventricular tachycardia due to coronary heart disease. It should be considered in patients participating in strenuous athletic activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 14 publications
1
15
0
Order By: Relevance
“…The initiation of VT was associated with a typical catecholamine surge seen on exercise in the setting of the presence of arrhythmogenic substrate characteristic of these patients. 21,22) Therefore, as exercise may increase heart rate in a pregnant woman with a diagnosis of ARVC, it is better to recommend to avoid exercise.…”
Section: Discussionmentioning
confidence: 99%
“…The initiation of VT was associated with a typical catecholamine surge seen on exercise in the setting of the presence of arrhythmogenic substrate characteristic of these patients. 21,22) Therefore, as exercise may increase heart rate in a pregnant woman with a diagnosis of ARVC, it is better to recommend to avoid exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Strenuous exercise, sport and acute mental stress are major triggering factors (23-100%) of SCD in patients with RVC [324][325][326][327] . Patients with RVC should therefore be strongly discouraged from practicing competitive sports.…”
Section: Management Of High Risk Patientsmentioning
confidence: 99%
“…It has been shown that physical exercise is a precipitating factor for lethal ventricular arrhythmias in patients with ARVC. 5 Corrado et al 27 reported that sudden cardiac death occurred among young ARVC patients, and Leclercq et al 28 documented VT on a 24-hour Holter ECG after an autonomic imbalance of increasing sympathetic tone in ARVC patients. Furthermore, it has been reported that adrenergic stimulation, an isoproterenol infusion mimicking the catecholamine effect, induced VT with ARVC.…”
Section: Discussionmentioning
confidence: 99%